Physicochemical and sensory properties of a traditional chilli shrimp paste. - Sobhi, Babak; Mohd Adzahan, Noranizan; Abdul Karim, Muhammad Shahrim; Karim, Roselina (Wfl Publisher, 2010)
Chilli shrimp paste is a traditional Southeast Asian condiment, usually consumed uncooked as a side dish with meal or raw vegetables. Chilli shrimp paste conventionally is prepared by housewives at home or at the restaurants using toasted fermented shrimp and fresh red chillies which are ground together with a granite mortar and pestle. The physicochemical properties and consumer preference of different chilli shrimp pastes were determined. The analyses were carried out using products obtained from the hypermarkets (commercially processed), restaurants (fresh made), and a product made in the laboratory by a professional chef. The colour value, pH, total soluble solids, moisture content, salt and sucrose were investigated. The results indicated that chilli shrimp paste with approximately 70% moisture content, 27 °Brix, 4.4% salt, 10% sucrose, thick and chunky paste with lightness value (L) of 23, redness value (a) of more than 20 and yellowness value (b) of 12 was more preferred. The linear model was found to describe the correlation between panellist score and colour values. Based on the model, panellists like redness and lightness but not yellowness. The highest coefficient of (a) value shows the most effective factor in colour score by panellist was redness. The pH range of samples was from 4.02 to 6.33. The pH of the samples did not affect the preference. Chilli shrimp paste prepared in the laboratory was most preferred while the commercially processed product was least preferred. The provided information in this study will help those in the food service industry to improve their products to meet consumer demand.